Analisis Mekanisme Penyelenggara Kliring Lokal Manual Pada Kantor Perwakilan Bank Indonesia Provinsi Sumatera Utara - Lamtiur Simamora; Gulo, Ayu Lestari; Lumban Gaol, Ayu Indah; Gultom, Intan Angelina; Br Sinambela, Putri Yulia; Christnova Hasugian; Hamonangan Siallagan (LPPM POLITEKNIK LP3I BANDUNG, 2024)
The aim of this research is to determine the mechanism for implementing clearing at the Bank Indonesia Representative Office (KPW) of North Sumatra Province. In analyzing the data, the author used a qualitative data analysis method as a research method that explains descriptively the clearing implementation mechanism at the Bank Indonesia Representative Office, North Sumatra Province. Clearing as one of the payment and collection services for customers at the Bank Indonesia Representative Office of North Sumatra Province, in its implementation carries out the process of debit clearing activities. Based on the explanation of the existing clearing implementation mechanism and determined by the Bank Indonesia Representative Office of North Sumatra Province, it can be concluded that the clearing implementation mechanism implemented is in accordance with the systems and mechanisms of the Bank Indonesia National Clearing System (SKNBI) and has been well realized, so that the level the occurrence of mistakes or mistakes can be minimized. However, sometimes the clearing implementation experiences obstacles that hinder the clearing process. The obstacle in question is a disruption in connection with the national clearing organizer (Central BI Office) in carrying out online clearing because there are too many clearing participants carrying out online clearing. This has an impact on clearing activities which causes delays both in obtaining data and in sending clearing data.